Comparative bio-efficacy of zinc fortified phosphatic fertilizers in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system in north-western India - SAINI, SAT PAL; DHERI, G S; SINGH, PRITPAL (The Indian Journal of Agricultural Sciences, 2021)
The field experiments were conducted during 2015-16 at five different locations in Punjab, north-western India to study the effect of soil and foliar application of zinc (Zn) either along with ordinary P fertilizers (DAP and SSP) or through their fortified sources (ZnDAP and ZnSSP). The field treatments consisted of control (NK), NK+ DAP, NK+ SSP, NK+ ZnDAP (ZnDAP), NK+ ZnSSP (ZnSSP), Zn (Zn spray), NK+ ZnDAP+ Zn spray (ZnDAP+ Zn spray) and NK+ ZnSSP+ Zn spray (ZnSSP+Zn spray) in a rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system. The application of ZnDAP increased wheat grain yield by 4.1-5.8%, compared with control at different experimental sites. The ZnDAP+ Zn spray and ZnSSP+Zn spray significantly increased the wheat straw yield by 20.1 and 23.4%, respectively compared with the control. The increase in Zn concentration in wheat grains significantly (R2=0.950- 0.986**, P<0.01) increased the wheat grain yield. The application of ZnDAP and ZnSSP significantly increased the Zn concentration in wheat straw by 19.0 and 27.6%, compared with control. The ZnDAP+ Zn spray and ZnSSP+Zn spray significantly increased the rice grain yield by 14.4 and 16.5%, respectively, compared with control. The increased Zn concentration in rice grains significantly (R2=0.756*, P<0.05 to 0.973**, P<0.01) increased the rice grain yield at different experimental sites.